Studi Penggunaan Bahasa Slang pada Platform Media Sosial Instagram - Marzuki Marzuki; Juni Ahyar; Teuku Azhari (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to describe forms of slang in the comments column on the Instagram account @jendamclover. This type of research is qualitative research. The data in this research is the slang language found in the comments column of the Instagram account @jendamclover. The data source in this research is the Instagram account @jendamclover. Data collection techniques in this research are observation techniques, documentation techniques, and transcription techniques. The results of the research show that the forms of use of slang in the comments column of the Instagram account @jendamclover consist of four forms, namely abbreviations, abbreviations, contractions and acronyms. The research data was found in the Instagram account @jendamclover as many as 58 data, consisting of 21 data in abbreviated form, 9 data in cutting form, 26 data in contraction form, and 2 data in acronym form.